Various Book Reviews - Editor, van der Waag (Scientia Militaria - South African Journal of Military Studies, 2017)
1. Warfare and Tracking in Africa, 1952-1990. 2. A Far-Away War: Angola, 1975-1989. 3. Iron Fist from the Sea: South Africa’s Seaborne Raiders 1978-1988. 4. 24 Hours at Waterloo, 18 June 1815.